Vicious cycle of oxidative stress and neuroinflammation in pathophysiology of chronic vascular encephalopathy - Dmytriv, Tetiana R.; Duve, Khrystyna V.; Storey, Kenneth B.; Lushchak, Volodymyr I. (Frontiers in Physiology, 2024)
Chronic vascular encephalopathy (CVE) is a frequent cause of vascular mild cognitive impairment and dementia, which significantly worsens the quality of life, especially in the elderly population. CVE occurs as a result of chronic cerebral hypoperfusion, characterized by prolonged limited blood flow to the brain. This causes insufficient oxygenation of the brain leading to hypoxia. The latter triggers a series of events associated with the development of oxidative stress and neuroinflammation, causing neurodegeneration. This review is focused on the significance of these processes in the pathophysiology of CVE. We consider the molecular mechanisms of oxidative and reductive stresses induced by hypoxia and reoxygenation and the development of neuroinflammation in CVE, combining them into a vicious cycle of neurodegeneration. We also discuss the prospects of using sulforaphane, an isocyanate common in cruciferous plants, and vitamin D to break the vicious cycle and alleviate the cognitive impairments characteristic of patients with CVE.